2018
DOI: 10.1039/c8cs00106e
|View full text |Cite
|
Sign up to set email alerts
|

Single-molecule protein sensing in a nanopore: a tutorial

Abstract: Proteins are the structural elements and machinery of life responsible for a functioning biological architecture and homeostasis. Advances in nanotechnology are catalyzing key breakthroughs in many areas, including the analysis and study of proteins at the single-molecule level. Nanopore sensing is at the forefront of this revolution. This tutorial review provides readers a guidebook and reference for detecting and characterizing proteins at the single-molecule level using nanopores. Specifically, the review d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
226
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 235 publications
(239 citation statements)
references
References 50 publications
2
226
1
Order By: Relevance
“…While the volume-based model in Equation 2 accurately describes streptavidin's translocation at low voltage, it does not address the effects of protein orientation (relative to the pore axis) or of conformational changes which become increasingly likely at higher voltages that favor protein shearing. (46,47) Recently, Yusko(19) and Houghtaling et al (40) developed a model linked to Maxwell's derivation:…”
Section: Monovalent Streptavidinmentioning
confidence: 99%
See 1 more Smart Citation
“…While the volume-based model in Equation 2 accurately describes streptavidin's translocation at low voltage, it does not address the effects of protein orientation (relative to the pore axis) or of conformational changes which become increasingly likely at higher voltages that favor protein shearing. (46,47) Recently, Yusko(19) and Houghtaling et al (40) developed a model linked to Maxwell's derivation:…”
Section: Monovalent Streptavidinmentioning
confidence: 99%
“…(60, 61) Further, the stochastic nature of translocation-induced conformational deformation produces a broader distribution of dwell times. (47) The most likely explanation for the decreased blockage depth and increased dwell time is a partial unfolding or restructuring of the protein under the larger force of a 600 mV applied bias.…”
Section: Monovalent Streptavidinmentioning
confidence: 99%
“…As expected, we observed transient dips in the current through the bare pore upon injection of the proteins, which we attribute to single-molecule translocations of the analyte molecules. As is typical in nanopore experiments, translocation events yield current blockades with a characteristic amplitude and dwell time, where the former relates to the size of the molecule occupying the pore and the latter generally depends on specific interaction between the translocating molecule and the pore wall 55 . Next, we repeated the experiment under identical conditions on the same pore after coating with NupX took place ( Figure 3b).…”
Section: Single-molecule Translocation Experiments With Nupx-coated Nmentioning
confidence: 99%
“…1384pF (1) CSi-B2 +C Si Table S3. The calculation of the sapphire nanopore capacitance in Figure S1d.…”
Section: Csi-b1mentioning
confidence: 99%
“…Further, we have demonstrated that a sapphire nanopore 23 chip (~7 nm pore diameter in a 30 nm thick and 70 µm wide SiN membrane) has more than two-24 order-of-magnitude smaller device capacitance (10 pF) compared to a float-zone Si based 25 nanopore chip (4 nm pore in 23 nm thick and ~4 µm wide SiN membrane, ~1.3 nF), despite having 26 a 100 times larger membrane area. The sapphire chip has a current noise of 18 pA over 100 kHz 27 bandwidth at a 50 mV bias, much smaller than that from the Si chip (46 pA) and only slightly 28 Introduction 34 Solid-state nanopores have attracted a lot of interest as a potentially high-speed, portable and 35 low-cost solution for detecting a variety of biomolecules, such as proteins 1,2,3,4 , RNA 5, 6, 7 and 36 DNA 8, 9, 10 , and studying molecular interactions 11,12 . However, fundamental limitations in design 37 and manufacturing of low-noise nanopore devices still remain.…”
mentioning
confidence: 99%